Clinical efficacy of intracavernous injection of platelet lysate for erectile dysfunction - Yi-Kai Chang; I-Ni Chiang; Hong-Chiang Chang; Yi-Hui Chen; Shih-Chieh Jeff Chueh (BMC Urology)
Abstract Background Among the emerging treatments for erectile dysfunction (ED), platelet-rich plasma (PRP), known for its ability to enhance tissue repair and regeneration, stands out as a promising therapeutic approach. In this innovative study, we aimed to assess the efficacy of intracavernous injections of platelet lysate (PL), a derivative of PRP, in improving erectile function among ED patients. Methods We enrolled twenty-six patients, aged between 35 and 70 years (mean age 51.6 ± 11.3 years), who had been experiencing ED for over six months and had an International Index of Erectile Function-5 (IIEF-5) score of 21 or less. Participants received autologous PL injections intracavernously every two weeks for a total of five administrations. We assessed Erection Hardness Score (EHS) and International Index of Erectile Function-5 (IIEF-5) bi-weekly for 16 weeks and conducted penile Doppler ultrasounds pre- and post-treatment to record peak systolic velocity (PSV) and resistance index (RI). Results Before treatment, the mean EHS was 2.15 ± 0.88 and IIEF-5 was 10.92 ± 5.28. Remarkable improvements were observed post-treatment, with the EHS significantly increasing to 3.15 ± 0.83 (p < 0.05) and IIEF-5 to 17.23 ± 5.26 (p < 0.05). Penile Doppler ultrasound exhibited an increase in both PSV and RI post-treatment, with the rise in RI being statistically significant. Conclusions Our findings indicate that intracavernous injections of PL substantially enhance erectile function, as evidenced by improvements in EHS, IIEF-5, and the RI of penile Doppler ultrasound, without hemorrhagic events or other adverse reactions apart from temporary pain at the injection site during the 16-week follow-up period. These encouraging results suggest that PL injections are a safe and effective treatment modality for patients with moderate ED, potentially providing a less invasive and more physiologically friendly alternative to current ED management strategies. Trial registration The study received approval from the Institutional Review Board of National Taiwan University Hospital (IRB Number 202008061RIPC, date of registration 08/28/2020).